Effect of Marginal Zinc Intake and Repletion on Essential Fatty Acid Metabolism - Suh, Jung; Burke, Sarah; Shigenaga, Mark; Killela, David; Holland, Tai; Shenvi, Swapna; Sutherland, Barbara; King, Janet C. (2017)
Objective To determine the effects of marginal zinc deficiency and repletion on essential fatty acid, sphingolipid, and lipoprotein metabolism. Methods Sixteen apparently healthy male subjects between ages of 18–45 were subjected to three sequential phases of dietary zinc intake modulation: Phase 1: Low Zinc intake: 6 mg/day with 1.5 g of phytate (2 wks); Phase II: Zinc Repletion: 10 mg/day with no phytate (4 wks); Phase III: Zinc Supplementation: Ad lib diet supplemented with 20 mg zinc (2 wks). Subject weight, and compliance with diet were monitored every 3–4 days during the first two phases. Plasma free fatty acids and sphingolipids were measured by mass spectrometry. FADS1 and FADS2 activities were calculated by g-linolenic (GLA)/linolenic acid (LA) or arachidonic acid (AA)/dihomo-g-linolenic acid (DGLA) ratios, respectively. Results Plasma zinc levels remained unchanged during Phases I and II in all subjects and increased only at the conclusion of phase III. FADS1 activity significantly (p=0.005) decreased from 5.2 ± 0.5 to 3.6 ± 0.5 (mean ± SEM) following Zn depletion. In contrast, FADS2 activity was insensitive to effects of low zinc intake. As a consequence of FADS1 activity loss, concentrations of AA-containing phosphatidylcholine (PC), phosphatidylethanolamine (PE), sphingomyelins and plasmalogen antioxidant lipids decreased significantly. Furthermore, plasma concentrations of C16:0 ceramide increased following Zn depletion (p = 0.06) and was inversely correlated with FADS1 activity (p = 0.04; r2 = 0.6). Zn depletion also increased plasma triglyceride (TG) by 26 ± 15% (p< 0.05) and decreased high-density lipoprotein (HDL) by 18.5 ± 3%; P<0.05. Interestingly, changes in FADS1 activity observed during the depletion was not normalized by dietary Zn repletion (Phase II) but, it was completely normalized with Zn supplementation (20 mg/day; Phase III). Conclusion Dietary Zn depletion (6 mg/day) decreases FADS1 activity and lowered AA incorporation into major lipid sub-classes. Loss in FADS1 activity was inversely correlated with C16:0 ceramide and was further associated with dyslipidemia as evidenced by significant alterations in plasma TG and HDL. These effects were not corrected with dietary Zn repletion (10 mg/day); supplementation with 20 mg Zn/d for an additional 3 weeks was required. These data suggest that FADS1 activity may be a sensitive biomarker of inadequate zinc intake and they also implicate marginal Zn intake as a novel risk factor for dyslipidemia and insulin resistance. Support or Funding Information Harvest Plus, NIH S10OD0018070-01